Pengaruh Endorser Blackpink dan Daya Tarik Iklan di Media Sosial Instagram Terhadap Keputusan Pembelian Oreo Blackpink - Nadya Safira; Syafrida Nurrachmi Febriyanti (Lembaga Pengembangan Kinerja Dosen, 2024)
The use of a well-known and respected individual in the realms of art, entertainment, athletics, or public relations to promote a product or service is known as a celebrity endorsement. Finding out how much of an impact Blackpink endorsers and Instagram ads have on consumers' propensity to buy is the driving force behind this study. Dark-skinned Oreos. Descriptive quantitative research using survey methodologies is used. One hundred students from UPN Surabaya made up the group surveyed for this study. Probability sampling using a simple random sample approach is used in the sampling process. Primary data is used in this study data gathering approach. Based on the study findings, the celebrity endorser variable is statistically significant (p < 0.05) with a t-value of 2.993 > 0.05. With a sig value of 0.015 < 0.05 and a computed t value of 2.483 > t table 1.985, the advertising attractiveness variable is statistically significant (t table 1.985). The findings indicate that the significance level is less than 0.05, with a F value of 26,720, which is more than the number in the F table, which is 3.09. The R-squared value is 0.355 and the multiple correlation result is 0.596. Celebrity endorsements, the beauty of Instagram ads, and the attractiveness of Instagram ads all had a role in influencing consumers' choices to buy Blackpink Oreos.